Effect of water velocity on the physiology of a collapsing Sargassum siliquastrum canopy under a controlled environment. Issue 4 (25th August 2020) - Inoue, Yukio; Terada, Ryuta; Belleza, Dominic F. C.; Nishihara, Gregory N.
SUMMARY: Seaweed beds form a canopy affecting water flow in and around them, and therefore affect mass transport processes between the canopy and the surrounding seawater. Nutrients and physiological byproducts are transferred to and from the bulk seawater and the macroalgae surface, where they are absorbed or released. A change in the canopy structure caused by the interaction of the canopy with water motion affects mass transport and therefore affects physiological rates. Many previous studies reported that photosynthesis and nutrient uptake rates increase as water velocity increases, and recent studies have begun to examine how the interaction between water velocity and canopies affects mass transport. To elucidate how this interaction can affect the physiology of macroalgae, we measured the spatial distribution of water velocity around and in a Sargassum siliquastrum canopy and examined its impact on photosynthesis and dark respiration in a re‐circulating flume. We examined eight water velocities ranging from 0.5 to 40 cm s −1 and three canopy densities, where the spacings between individuals were 4, 6, and 8 cm. Dissolved oxygen concentrations were measured at each velocity for 2 h under dark conditions and for 1 h under 800 μmol photons m −2 s −1 . As water velocity increased, the canopy began to bend with the flow and collapse, which was quantified by digital images. The gross photosynthesis rate and the dark respiration rate of the canopy increased as water velocity increased. However, the gross photosynthesis rates began to decrease beyond 9 cm s −1, whereas the dark respiration rates began to decrease beyond 4 cm s −1 . Canopy density did not influence either of the rates. We conclude that increasing water velocities led to a collapse of the canopy, which inhibited water exchange between the canopy exterior and interior, and further led to the decline in physiological rates at high water velocity.